Intellectual Property, Developing Countries and the Law and Policy of the European Union : Towards Postcolonial Control of Development - Acquah, Daniel Opoku (IPR University Center, 2017)
The control of knowledge and information in the 21st century is a battleground. The reason is simple: information has become a ‘prime resource’ in modern economic life. The complex ecosystem of information is encapsulated in legal parlance as intellectual property. Characteristically intellectual property regimes create policy restrictions, in the form of exclusive rights to commercial use, on the otherwise free availability of knowledge and information in order to compensate for the cost of production of the knowledge or information. The exclusive rights, in effect, make access a saleable commodity and create the basis of markets for knowledge and technology. While these exclusive rights enable knowledge and technology markets, they also create social tension over the price of access and the lack of access. We have seen this tension played out in relation to access to medicines and biomedical technologies. This thesis attempted to provide the first integrative analysis of how the EU’s rulemaking on intellectual property, both at home and abroad, impacts the ability of developing countries to utilize the flexibilities flowing from the TRIPS Agreement to promote public health and access to medicines. The EU’s intellectual property policy has been conceptualized as comprising two distinct but intertwined normative regimes – the internal and external. The thesis argues that the EU’s internal and external intellectual property policies have developed in manners that are tightly intertwined and detrimental to developing countries’ ability to promote public health and access to medicines. It problematizes the issue in the context of postcolonial theory, supplemented by other theories. This theory underscores the notion that the overly compliant attitude of most developing countries towards international intellectual property laws – despite their obvious effects on their economies – goes beyond contemporary political and economic circumstances. It can be attributed to the colonial roots and neo-colonial structures of this body of law, perpetrated through the EU’s internal and external policy. The development of this law has been complicit in legitimizing the economic control of developing countries at the expense of their development. The overall finding is that the current EU intellectual property policy making approach, both at home and abroad, does not offer the necessary freedom for development in developing countries. It simply works to protect the EU’s industrial interest, with serious implications for public health. This observation is supported by the findings of five individual essays, which recommends, among others, for the EU to streamline its development, industrial and trade policies in ways that could simultaneously meet the development and health care needs of developing countries and the EU’s economic interest. Externally, it recommends that developing countries should not be forced to adopt the kind of laws discussed in this thesis through Free Trade Agreements. If they are, the following measures should be considered: (1) inclusion of a clause on transitional arrangements for developing countries specific to intellectual property in the Free Trade Agreements; (2) inclusion of a mandatory clause that clearly links the objectives for intellectual property protection and enforcement to a balance between the promotion of technological innovation and access to medicines; (3) framing the provisions on public health in the Free Trade Agreements as mandatory requirements or express exceptions, which will stipulate that the implementation of the Free Trade Agreement cannot lead to derogation from the protection of public health; (4) the inclusion of strong and comprehensive sustainable development chapters in the Free Trade Agreements, which are to be effectively implemented and enforced; and (5) allowing for reservations within the meaning of Article 19, Vienna Convention on the Law of Treaties in future Free Trade Agreements. Finally, the concept of substantive equilibrium has been proposed as a means of delinking the EU’s intellectual property policy from post-colonialism.

Informaation ja tiedon hallinta on 2000-luvun taistelukenttä. Syy tähän on yksinkertainen: tieto on nykypäivän talouselämän keskeisin resurssi. Tiedon monitahoinen ekosysteemi hahmottuu oikeuden näkökulmasta pitkälti immateriaalioikeuksien kautta. Tyypillisesti immateriaalioikeudet asettavat rajoitteita informaation ja tiedon muutoin vapaalle saatavuudelle määrittelemällä yksinoikeuden kaupalliseen käyttöön korvaukseksi tietämyksen ja tiedon tuottamiseen liittyvistä kuluista. Tosiasiallisesti tällainen yksinoikeus muuttaa käyttöoikeuden myytäväksi hyödykkeeksi ja luo pohjan tietämyksen ja teknologian markkinoille. Sen lisäksi, että yksinoikeudet mahdollistavat tietämyksen ja teknologian markkinat, ne luovat myös sosiaalista jännitettä siihen, millä hinnalla tietämys ja teknologia ovat käytettävissä, jos ylipäätään ovat. Näitä jännitteitä olemme jo nähneet, kun kyse on ollut esimerkiksi lääkkeiden saatavuudesta ja biolääketieteen tekniikoista. Tämän väitöskirjan tavoitteena oli analysoida, miten EU:n immateriaalioikeuksia koskevat määräykset – sekä EU:n sisäisesti että sen ulkosuhteissa – vaikuttavat kehittyvien maiden kykyyn hyödyntää TRIPS-sopimukseen sisältyviä joustomahdollisuuksia kansanterveyden ja lääkkeiden saatavuuden edistämiseksi. EU:n immateriaalioikeuspolitiikka on käsitteellistetty kattamaan kaksi erillistä mutta toisiinsa kietoutuvaa normatiivista menettelytapaa: sisäinen ja ulkoinen politiikka. Väitöskirjassa argumentoidaan, että EU:n sisäinen ja ulkoinen immateriaalioikeuspolitiikka ovat kehittyneet tiiviisti sidoksissa toisiinsa. Ne vaikuttavat haitallisesti kehittyvien maiden kykyyn edistää kansanterveyttä ja parantaa lääkkeiden saatavuutta. Väitöskirjassa problematisoidaan tätä jälkikoloniaalisen teorian ja täydentävien muiden teorioiden valossa. Tässä teoriassa korostetaan, että useimpien kehittyvien maiden kovin alistuvainen suhtautuminen kansainvälisiin immateriaalinormeihin – huolimatta niiden ilmeisistä haitallisistavaikutuksista kyseisten maiden talouteen – nousee vallitsevia poliittisia ja taloudellisia olosuhteita tärkeämmäksi. Syy tähän on löydettävissä näiden normien koloniaalisista juurista ja uuskoloniaalisista rakenteista, jotka heijastuvat EU:n sisäiseen ja ulkoiseen politiikkaan. Kyseisten normien kehitys on osaltaan ollut oikeuttamassa kehittyvien maiden talouden hallitsemista maiden kehityksen kustannuksella. Johtopäätöksenä väitöskirjassa todetaan, että EU:n nykyinen sisäinen ja ulkoinen immateriaalioikeuspolitiikka ei tarjoa riittävää vapautta kehityksen mahdollistamiseksi kehittyvissä maissa. Se yksinkertaisesti suojelee EU:n elinkeinoelämän etuja, millä on vakavia kansanterveydellisiä seurauksia. Havaintoa tukevat viiden eri artikkelin tulokset, joiden pohjalta suositellaan muun muassa, että EU virtaviivaistaisi kehitys-, teollisuus- ja kauppapolitiikkojaan siten, että ne samanaikaisesti täyttäisivät kehittyvien maiden kehitys- ja terveydenhoitotarpeet ja olisivat EU:n taloudellisten etujen mukaisia. EU:n ulkosuhteiden osalta suositellaan, että kehittyviä maita ei pakotettaisi hyväksymään tässä opinnäytetyössä kuvatun kaltaisia normeja vapaakauppasopimusten kautta. Mikäli näin kuitenkin tehdään, seuraavia toimenpiteitä tulisi harkita: (1) kehittyvien maiden siirtymätoimenpiteitä koskevan lausekkeen lisääminen vapaakauppasopimuksiin immateriaalioikeuksien osalta; (2) pakollinen lauseke, jossa selkeästi yhdistetään toisiinsa immateriaalioikeuksien suojelun ja toimeenpanon tavoitteet ja pyrkimys löytää tasapaino teknisen innovoinnin edistämisen ja lääkkeiden saatavuuden välillä; (3) kansanterveyttä koskevien säännösten merkitseminen vapaakauppasopimuksissa pakollisiksi säännöksiksi tai erityisiksi poikkeuksiksi, joissa määrätään, että vapaakauppasopimuksen toteuttaminen ei voi johtaa kansanterveyden turvaamisen huonontumiseen; (4) voimakkaiden ja kokonaisvaltaisten, kestävää kehitystä koskevien lukujen lisääminen vapaakauppasopimuksiin, joita tulee toteuttaa ja toimeenpanna tehokkaasti; ja (5) mahdollisuus valtiosopimusoikeutta koskevan Wienin sopimuksen artiklassa 19 tarkoitettuihin varaumiin tulevissa vapaakauppasopimuksissa. Lopuksi on ehdotettu aineellisoikeudellinen tasapaino -käsitettä keinoksi tehdä selvä ero EU:n immateriaalioikeuspolitiikan ja jälkikolonialismin välille.